Endoscopic lung volume reduction - Herth, Felix; Gompelmann, Daniela; Ernst, Armin; Eberhardt, Ralf (Respiration, 2009)
Chronic obstructive pulmonary disease (COPD) is a category of diseases characterized by chronic airflow obstruction and hyperinflation. The GOLD committee and the American Thoracic Society/European Respiratory Society have published detailed, evidence-based reviews of management approaches, providing stepped-care algorithms for pharmacologic and nonpharmacologic therapy. Over the past several decades, much effort was spent in designing additional nonpharmacologic approaches to ameliorate symptoms in these patients. Three endoscopic lung volume reduction principles have shown promise and reached later-stage clinical trials in patients with heterogeneous emphysematous diseases. These include so-called blocking devices (valves), nonblocking devices (coils) and irreversible nonblocking techniques (bronchoscopic thermal vapor ablation, polymeric lung volume reduction) designed to collapse and remodel hyperinflated lung. For homogeneous diseases the formation of airway bypass tracts designed to facilitate emptying of damaged lung regions with long expiratory times is being investigated.
Gesehen am 03.05.2023